MODELLING USER BEHAVIOR IN SUPER APPS: INTEGRATING TRUST AND PERSONAL INNOVATIVENESS INTO THE UTAUT3 FRAMEWORK FOR GOJEK - Antonio, Gregorius Rudy; Kurniawan, Michelle Petrice (UTSAHA: Journal of Entrepreneurship, 2025)
The rapid advancement of digital technology has fostered the rise of super apps, multifunctional platforms that consolidate services such as ride-hailing, digital payments, and food delivery. In Indonesia, Gojek exemplifies this trend, particularly among university students, who represent tech-savvy early adopters. However, current research applying the Unified Theory of Acceptance and Use of Technology 3 (UTAUT3) to such complex digital ecosystems remains limited. This study addresses the theoretical and empirical gaps by examining the behavioral intention and actual usage of Gojek among students at University X using an extended UTAUT3 framework, which incorporates trust and personal innovativeness. Employing a quantitative approach, primary data were collected via an online questionnaire distributed to students from the 2021–2024 cohorts. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). Results revealed that all 12 main UTAUT3 constructs significantly influenced behavioral intention and use behavior, with habit, social influence, and facilitating conditions emerging as the strongest predictors. Meanwhile, price value showed a negative influence, highlighting cost sensitivity. Among the 26 moderation hypotheses, only three were accepted, with user experience moderately enhancing the link between intention and actual use. These findings provide both theoretical insights into the applicability of UTAUT3 in super app contexts and practical implications for enhancing user engagement strategies within the digital platform economy.